Workshops for the promotion of health with adolescents: experience report - Almeida, Janaína Rocha de Sousa; Oliveira, Nancy Costa de; Moura, Escolástica Rejane Ferreira; Sabóia, Vicente de Paulo Aragão; Mota, Maria Vaudelice; Pinho, Luciana Gonçalves Maciel (Rev Rene, 2011)
The need to develop actions that target adolescents’ health has become imperative in the face of expressiveness they present for both the overall population as well as their significance in terms of future generation. The aim of this research is to report the work of health education with adolescents, accomplished through workshops, contributing to develop new activities seeking health promotion. This is a descriptive study regarding the activities of the Program on Education for Health (Health PET) held from October to December 2009. The workshops took place in a public school, in Fortaleza-Ceará. The themes discussed were suggested by the adolescents themselves and grouped like the following: Sexuality, drugs, violence, adolescent health. There was a need to adopt educational practices of the character of dialogue with active participation of adolescents so they feel subject, co-responsible for their health and improvement in their quality of life. This study emphasized the importance of links with schools and the importance of intersectoral and multidisciplinary approach.